2019
DOI: 10.3390/polym11101696
|View full text |Cite
|
Sign up to set email alerts
|

Side Chain Effect of Hydroxypropyl Cellulose Derivatives on Reflection Properties

Abstract: Some cellulose derivatives are known to exhibit thermotropic and lyotropic cholesteric liquid crystal (CLC) phases with a visible reflection feature by changing the side chains and mixing with specific solvents, respectively. Although many studies have been reported so far, most of the derivatives have the side chains of linear alkyl groups, but not the bulky phenyl groups. In this report, we synthesized a series of hydroxypropyl cellulose (HPC) derivatives that possessed both linear propionyl esters and bulky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…25 Some proteins, heterocyclic compounds, detergents, and cellulose derivatives can form LC mesophases. [26][27][28] With regard to cellulose derivatives, the ethyl cellulose (EC), hydroxypropyl cellulose and cellulose acetate are able to form both lytropic and thermotropic LC phases. These derivatives can form chiral nematic phase due to chairality (optical properties) of cellulose backbone and its rigid helical conformation.…”
Section: Introductionmentioning
confidence: 99%
“…25 Some proteins, heterocyclic compounds, detergents, and cellulose derivatives can form LC mesophases. [26][27][28] With regard to cellulose derivatives, the ethyl cellulose (EC), hydroxypropyl cellulose and cellulose acetate are able to form both lytropic and thermotropic LC phases. These derivatives can form chiral nematic phase due to chairality (optical properties) of cellulose backbone and its rigid helical conformation.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, the structural colours present in cellulosics are due to cholesteric phases that are obtained from lyotropic and/or thermotropic systems that were much studied in the eighties [12][13][14][15][16][17][18] . After the preliminary studies many other works were performed in order to obtain different coloured thermotropic cellulose derivatives, at room temperature, and to better understand the formation of right-and left-handedness in cellulose-based helicoidal liquid crystalline phases [19][20][21][22][23][24][25][26] . The photonic characteristics of the thermotropic, as well as lyotropic cellulosic systems, were found to depend on temperature, pressure, concentration, type of solvent and cellulose derivative.…”
Section: Introductionmentioning
confidence: 99%
“…These materials show characteristic optical textures similar to un-crosslinked cellulose-based liquid crystal polymers although welldefined patterns typical of cholesteric structures were not observed [66,67]. The esterification of HPC by a series of aliphatic acid esters exhibited characteristic features of cholesteric LC phases between their glass transition and isotropization temperatures [68,69]. This literature confirmed that an increase in the number of methylene units in the side chains of this series of aliphatic acid esters of (2-hydroxypropyl) cellulose, led to an increase in the layer spacing values for the cholesteric LC phases measured by WAXD.…”
Section: Cellulose-based Liquid Crystalmentioning
confidence: 99%